A free man of color - Hambly, Barbara (Bantam Books, 1998)
It is 1833. In the midst of Mardi Gras, Benjamin January, a Creole physician and music teacher, is playing piano at the Salle d'Orleans when the evenings festivities are interrupted--by murder.